113. Eligibility and feasibility of adjuvant breast cancer treatments with pencil beam scanning (PBS) proton therapy. An inter-institutional study. (December 2018) - Algranati, C.; Strigari, L.; Vennarini, S.; Pinnarò, P.; Fellin, F.; Sanguineti, G.; Amichetti, M.
Abstract : Purpose: Proton therapy reduces lung dose and mean heart dose in breast cancer irradiation in adjuvant breast cancer, in particular with nodal involvement[1] . In this work we compare 10 selected intensity modulated photon therapy (IMXT) treatment cases selected from the sending institution with PBS proton therapy. Methods and materials: The eligibly criteria of the sending institution were: poor coverage of the target volumes, unfavourable dose volume histograms (DVH) to the organs at risk (OAR) lung and heart or wide irradiated volume (IV) with static IMXT. The type of case were heterogeneous as shown in Table 1. All plans were performed on the CT and volumes send applying a class solution of 3 proton field with range shifter with treatment planning system (TPS) Raystation. All plans were performed in robust Single Field Optimization technique (rSFO) optimizing the target and the OAR heart and the ipsilateral lung. The optimization was done with clinical pencil beam algorithm and 5 mm geometrical robust optimization tool provided by the TPS. No robust optimization of the range was applied. Results: Comparing the proton and photon plans there was a significant improvement in at least one of the following parameter: IV, DVH of lung, DVH of heart for each case (e.g. Fig. 1). Conclusion: The results of this study are promising. The heuristic eligibility method provide positive answer in 100% of the cases. Further work are necessary to assess role of range errors of proton peak.